Shortened amoebapore analogs with enhanced antibacterial and cytolytic activity - Jörg Andrä and Otto Berninghausen and Jan Wülfken and Matthias Leippe (FEBS letters : for the rapid publication of short reports in biochemistry, biophysics, and molecular biology, 1996)
Amoebapores are cytolytic peptides of Entamoeba histolytica which function by the formation of ion channels in target cell membranes. Three isoforms (amoebapore A, B, and C) exist in amoebic cytoplasmic granules. They are composed of 77 amino acid residues arranged in four α-helical domains. In order to analyze the structure-function relationships, 15 synthetic peptides of 24–25 residues were constructed based on the assumption that the third helix is the membrane-penetrating domain and on the previous finding that positively charged residues are significant for activity. Activity of these short versions of Amoebapores was determined towards artificial and natural targets, such as liposomes, bacteria, erythrocytes and a human tumor cell line. It was found that some of the novel peptides were highly active and showed a broader activity spectrum compared to the parent molecules.
Keywords: Amoebapore; Antibacterial activity; Cytolysis; Pore formation; Synthetic peptide; Entamoeba histolytica